Application of Simple Database Algorithm and Big Data Technology in College Student Information System - Wang, Qian (International Conference on Inventive Computation Technologies (Online), 2022)
Application of simple database algorithm and big data technology in college student information system is studied in this paper. Kubernetes mainly includes functional modules such as automatic deployment of container clusters, automatic scaling, and container maintenance and also the management. Kubernetes defeated Swarm and Apache Mesos to become the de facto standard for container cluster management. Kubernetes clusters achieve unified cluster management and maintenance of resource objects through abstracted API interfaces. The designed data packet arrives at the VPN pod. According to the source address of the data packet, the security policy is searched, and the corresponding unpacking work is performed. According to the security policy, the internal network interface is sent to the canal0 device of the calico network. Then the model will be applied to the designed framework.